Integration of Religion and Science as a Pillar of Harmony of Spirituality and Rationality in Building a Sustainable Civilization - Khairina; Haris Riadi; Edi Prasetyo; Rusiah; Muhadi; Rajuna (al-Afkar, Journal For Islamic Studies, 2026)
This paper discusses the importance of integrating religion and science in education and scientific development. This integration aims to eliminate the dichotomy between religion and science that has created a gap. With a holistic approach, Islamic religious education can be contextualized alongside science, creating a generation that masters both worldly knowledge and spirituality. This article outlines the meaning, goals, and urgency of integrating religion and science in addressing the challenges of globalization and modernization. The conclusion suggests that an integrative educational approach can strengthen the harmony between religion and science to build a better human civilization.